Bibliometric analysis of document flow in the field of library-bibliography in Azerbaijan - Bayramova, Irada (Technium Social Sciences Journal, 2022)
In the article, the issues of creation and development of the document flow in the field of library-bibliography in Azerbaijan in modern times are reflected from a statistical point of view. Preliminary considerations on the mentioned problem have been examined here. In the article, the flow of documents in the field is grouped and analyzed according to specific indicators. Journals in the field were identified, "Library Studies and Bibliography" magazine was included in the research according to certain characteristics, and tables and graphs were prepared on the results obtained. In addition, the work experience of the Azerbaijan National Library was applied for the purpose of researching the activities of institutions that create and study the flow of documents in the field of library and bibliography.